Photoredox Transformations with Dimeric Gold Complexes1. Issue 50 (16th October 2013) - Revol, Guillaume; McCallum, Terry; Morin, Mathieu; Gagosz, Fabien; Barriault, Louis
<x xml:space="preserve">Abstract</x> Let the sunshine in! Unactivated alkyl and aryl bromides underwent a light‐enabled reductive radical cyclization in the presence of a dimeric phosphine–gold complex as a photocatalyst (see scheme; X=C(CO2Et)2, NR, O). Sunlight can be used as the energy source for this simple and efficient radical reaction, which does not require potentially hazardous and toxic chemical reagents, such as organostannanes and chemical initiators.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>